2014
DOI: 10.1111/boj.12147
|View full text |Cite
|
Sign up to set email alerts
|

The biogeography and genetic relationships ofJuniperus oxycedrusand related taxa from the Mediterranean and Macaronesian regions

Abstract: Despite Juniperus spp. being an important component of Mediterranean arid and semi‐arid ecosystems, there is a lack of complex studies on their biogeographical patterns. Using 16 morphological cone and seed traits and three nuclear microsatellite markers, we investigated the morphological and genetic variability of seven Mediterranean and Macaronesian Juniperus taxa (J. oxycedrus ssp. oxycedrus, J. oxycedrus ssp. badia, J. brevifolia, J. cedrus, J. deltoides, J. macrocarpa and J. navicularis) to identify bioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…The lack of direct dependency on most of the tested morphological characters on the climatic factors of particular populations (see above) can indicate the genetic condition of leaf morphology. Similar patterns of genetic and morphological differentiation of populations were found in several other species (e.g., compare Terrab et al 2008Terrab et al 2007with Sękiewicz et al 2013, see also Boratyński et al 2014). …”
Section: Multivariate Differences Between Populationssupporting
confidence: 72%
“…The lack of direct dependency on most of the tested morphological characters on the climatic factors of particular populations (see above) can indicate the genetic condition of leaf morphology. Similar patterns of genetic and morphological differentiation of populations were found in several other species (e.g., compare Terrab et al 2008Terrab et al 2007with Sękiewicz et al 2013, see also Boratyński et al 2014). …”
Section: Multivariate Differences Between Populationssupporting
confidence: 72%
“…However, a particular set of life-history traits that are found in tree species enable them to keep high within-population genetic diversity (Petit and Hampe 2006). High genetic diversity was observed in other coniferous species from the East Mediterranean (Dagher-Kharrat et al 2007;Douaihy et al 2011;Sobierajska 2012) and from the Mediterranean in general (Terrab et al 2007;Boratyński et al 2009;Liepelt et al 2010;Dzialuk et al 2011;Boratyński et al 2014). Higher levels of genetic variability observed in East Mediterranean species compared with West Mediterranean species is believed to be related to the relatively more stable palaeoenvironmental conditions prevailing in the eastern part of the region during the last glacial cycle (Fady and Conord 2010).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…However, our results are not final, mainly because nSSR-based genetic patterns do not have to follow taxonomic entities. There are some studies in which these kinds of markers helped to resolve taxonomic doubts or give some new insights (Boratyński et al 2014;Dering et al 2014), but generally reliable phylogenetic analysis requires the use of more appropriate markers and statistical tools.…”
Section: Pattern Of Differentiationmentioning
confidence: 99%
“…Influence of external factors on genetic diversity of the junipers including geographical proximity (Oostermeijer & Knegt, 2004;Sobierajska et al, 2016), long-term evolution (Hantemirova et al, 2012;Filipowicz et al, 2006;Meloni et al, 2006;Boratyński et al, 2014) has been shown in previous studies. However, there are only few studies where habitat-related peculiarities are mentioned: association between ISSR-related data and habitat type of populations have been described for J. brevifolia populations from the Azorean archipelago (Silva et al, 2011) and J. communis from Wales and England (Van der Merwe et al, 2000).…”
Section: Discussionmentioning
confidence: 62%